The Image of Women in English and Uzbek Literature - Gulsoraxon, Sultonboyeva (Journal of Innovation in Education and Social Research, 2024)
In the current globalization process, our people improving spiritual, political and religious literacy. The most important demand of our time is the issue of women is of particular importance. The article is in English and Uzbek prose characteristics of women's image are considered. Every nation is national based on his views on the image of a woman in his literature describes differently. In Uzbek prose, a woman is a mother, a wife, a housewife described as, and in English literature as an addition to these as well as tasks such as female business entrepreneur, working employee does. In English literature too, the image of a woman is gradual over the ages changed. Female characters in 19th century English prose male writers completely idealized by also. In our article, the relationship between women and society is also discussed in different ways is studied. Analyzing the literature, we see the image of a woman creation mainly from the relationship between women and society, women how it is recognized in society and in the family to evaluate the description of a woman in prose, analyzing her position possible As for the image of a woman in every national literature, it reflects the nature of that people, the spirit of the times, perception will be done.